ENERGY EFFICIENT MULTI-TIER SUSTAINABLE SECURE ROUTING PROTOCOL FOR MOBILE WIRELESS SENSOR NETWORKS - RAJ, JENNIFER S; Smys, S.; Bashar, Abul (IRO Journal on Sustainable Wireless Systems, 2019)
The advanced progress in wireless communication pays attention on information of more sensitivity to be delivered to its destined end with numerous of restrains, such as reliableness, constancy, response time and safety. The advancements in digital gadgetry, the usage of unwired transceivers and microcontrollers has made viable the integration of sensing and computing device with transceivers and power units to form a single unit called sensor nodes, the enveloping of sensor nodes form wireless sensor nodes. Innumerable existing proposals have aimed at the energy efficient and secure transmission of data but have achieved any one at the cost of the other. Noting down the issues of the existing method this paper proposes an energy efficient multi-tier sustainable secure routing protocol (EEMSR) for mobile wireless sensor nodes which is a cohabit of multi-tier secure routing with an AL (Ant Lion) optimizer (CoMSRALO) along with the prime curve cryptography supported by the routing formed in spherical structure. This better encryption and decryption method takes the edge of power consumption and offers control over the utilization of energy which is difficult to be achieved when dispatching the pack and also avoids the intervention of the encroacher and improves the security and minimizes the deprivation caused due the information lost.